Conceptualizing micro-adaptive teaching practices in content-specific ways: Case study on fractions - Prediger, Susanne; Quabeck, Kim; Erath, Kirstin (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
Adaptive teaching on the micro-level of teacher-student interaction has often been investigated, but rarely with respect to students’ content-specific learning pathways. In this paper, we present an analytic approach to disentangle the learning content into its components and to capture the content-specific adaptivity in teaching practices with respect to teachers’ student focus and goal focus. For this, adaptive teaching is conceptualized as teachers’ targeted steering trajectories navigating from students’ initial ideas towards the content goals. In a case study with video data from 19 middle school small-group sessions on comparing fractions in context problems, we show how the adaptivity of the teaching practices can differ with respect to student focus and goal focus even when the same teacher moves are used. This calls for extending professional development programs that combine working on teacher moves with unpacking content goals.